IMIPRAMINE INDUCED EXTRAPYRAMIDAL SYMPTOMS - Saha, Dr Amitabh; Duttta, Dr Bikram; Saini, Dr SK; Kumar, Dr Amit (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Extra pyramidal szymptoms are common side effets een with antipsychotics , however its association with tricyclics is rare but seen in clinical practice.A patient with Moderate depressive episode was managed with tricycyclic antidepressants. Patient developed acute dystonia on the third day and there were no additional medications he was prescribed. Tricyclic antidepressant (TCA)-related extra pyramidal side effects have been reported but these side effects are not well known. The prevalence and reporting of these side effects is low, despite widespread use of these medications. In some cases, it has also been seen to disappear even though the same dose of TCA is continued, and they do not seem to be a drug class reaction. It is also possible that . .